Dissociative features related to imaginary companions in the assessment of childhood adversity and dissociation: A pilot study - Huolman Mia; Peltonen Kirsi (Elsevier Masson s.r.l., 2022)
Childhood imaginary companions (ICs) are common and a normal part of child development, but certain aspects of ICs are also connected to adversity and dissociation. The purpose of this pilot study is to find out what kind of ICs children in mental health care have, are the features of ICs related to stressful childhood experiences, and whether the assessment of ICs could provide insight to the assessment of children. 19 7-12-year-old participants were recruited via a Finnish child psychiatry clinic. The children were interviewed using the imaginary companions interview. The legal guardians reported background information and information about stressful childhood experiences. The data was analyzed both quantitatively and qualitatively. In general, the ICs were more likely to have normative features than dissociative features. However, some dissociative IC features were also commonly reported. The SCE duration (U = 39.0, p = 0.029) and the number of dissociative IC features (U = 59.5, p = 0.005) were significantly higher for children with 6 or more ICs than for children with 1-2 ICs. There was a positive correlation between SCE duration and number of ICs (1-2 ICs vs. 6 or more ICs), r(12)) = 62, p = .018, and between dissociative IC features and number of ICs, r(15)) = 676, p = .003. Due to the small sample size in this study, the results cannot be generalized outside the clinical population with the specific age and symptom profile described in this study. Children were willing to talk about their ICs and interviewing them about their ICs seemed to add value to the assessments. Results and modifications made to the imaginary companions interview are discussed.